2006
DOI: 10.1016/j.molcel.2006.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Recapitulation of Short RNA-Directed Translational Gene Silencing In Vitro

Abstract: microRNAs (miRNAs) are a large class of endogenous short RNAs that repress gene expression. Many miRNAs are conserved throughout evolution, and dysregulation of miRNA pathways has been correlated with an increasing number of human diseases. In animals, miRNAs typically bind to the 3' untranslated region (3'UTR) of target mRNAs with imperfect sequence complementarity and repress translation. Despite their importance in regulating biological processes in numerous organisms, the mechanisms of miRNA function are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
139
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(154 citation statements)
references
References 39 publications
13
139
0
2
Order By: Relevance
“…Due to the limited requirement for sequence complementarity between a miRNA and a target transcript, any one miRNA has the potential to regulate the expression of many different genes. There is also supporting evidence for the multiple binding of miRNAs (whether the same or different) to unique sites within a single transcript and that the cumulative effect of these binding events may be required for maximal repression of translation [41].…”
Section: Microrna Biogenesis and Functionmentioning
confidence: 76%
“…Due to the limited requirement for sequence complementarity between a miRNA and a target transcript, any one miRNA has the potential to regulate the expression of many different genes. There is also supporting evidence for the multiple binding of miRNAs (whether the same or different) to unique sites within a single transcript and that the cumulative effect of these binding events may be required for maximal repression of translation [41].…”
Section: Microrna Biogenesis and Functionmentioning
confidence: 76%
“…However, mRNAs do not always respond with significantly decreased stability when targeted by miRNAs. (Humphreys et al, 2005;Pillai et al, 2005;Bhattacharyya et al, 2006;Petersen et al, 2006;Wang et al, 2006). miRNA targeted, translationally repressed transcripts can be transported to PBs without destruction suggesting that PB may function as a reservoir where quiescent mRNAs stored, possibly allowing their reuse for translation (Pillai et al, 2005;Bhattacharyya et al, 2006).…”
Section: Mechanism(s) Of Mirna-mediated Gene Regulationmentioning
confidence: 99%
“…It has been shown that reporter genes with the m 7 G-capped mRNA are repressed by miRNAs but not those with internal ribosome entry site sequences, suggesting some effect of miRNAs on initiation. 13 However, some miRNAs cause repression of mRNA with internal ribosome entry site sequences. 14 Also, polysomes cosediment with miRNAs and their target mRNAs, suggesting an influence on the elongation process of translation.…”
Section: Micrornas Regulate Gene Expressionmentioning
confidence: 99%